SYNTACTIC STRUCTURE OF THE SENTENCES IN JAMES ROSS’ THE CARD - Therina, Cindy; Yusmalinda, Yusmalinda (STBA Prayoga Padang, 2024)
Determining the sentences' syntactic structure was the research's main goal. Oneof the most important things to acquire in order to comprehend English isgrammatical structure. Understanding syntactic structure is crucial becausepoorly structured sentences might convey the wrong meaning. Syntacticstructure aids in word recognition, guarantees that sentences flow naturallytogether, and determines how words are arranged in lengthy phrases. The formsand functions of syntactic structure employed in James Ross' The Card are thetwo primary subjects of analysis in this study. This particular research isqualitative in nature. To be more precise, the writer gathered the informationthrough non-participatory observation. The majority of the findings on the formssupport Seely's (2012) postulated forms of syntactic structure. Subject, verb,object syntactic structure is the most common type. Then, the functions foundfully validate the syntactic structural functions described by Morley (2000).Nominal function is the primary function of syntactic structure.